The influence of spiritual brand attributes towards the corporate brand image of Islamic banking institutions in Malaysia - Siti Ngayesah Ab Hamid; Wan Jamaliah Wan Jusoh; Suharni Maulan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Incorporation of religious and spiritual values distinguishes the Islamic banking institution from its conventional counterpart. Yet, only a few studies concentrated to connect the spiritual aspects of Islamic banks with customers’ perceived image. This study attempts to determine the relationship of spiritual brand attributes, corporate brand image, and customer loyalty towards Islamic banking institutions in Malaysia. 499 questionnaires were administered and analysed using the Partial Least Square-Structural Equation Modeling technique. The findings indicate that ethics, corporate social responsibility, and beliefs are significant factors in influencing customers’ perception towards the corporate brand image of Islamic bank. In addition, corporate brand image is also significant in influencing loyalty. The study provides empirical evidence on the effects of a less investigated construct which is spiritual brand attribute towards image.